Leveraging Communication Analysis to Identify Key Challenges in an Innovation Course in computer science - Andrade, Múcio J. Alves de; Araújo, Cristiano C. de; Ramalho, Geber L. (Anais do Simpósio Brasileiro de Informática na Educação (SBIE), 2023)
This paper presents a case study investigating students’ main challenges in an undergraduate innovation course. The course follows a learning journey to discover opportunities, and design and implement innovative digital solutions. The results indicate that one of the main challenges students face is ineffective collaboration in multidisciplinary teams. While these challenges are complex for teachers to identify, they are evident in student communications on social tools. This research used data from interviews and communications analysis on social networks such as Whatsapp and Telegram to understand these challenges better.